Examples of solutions for steel-concrete composite structures in bridge engineering = Przykłady konstrukcji zespolonych w budownictwie mostowym - Flaga, Kazimierz; Furtak, Kazimierz (1951- ) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of the article was to discuss the application of steel-concrete composite structures in bridge engineering in the aspect of structural design, analysis and execution. It was pointed out that the concept of steel-concrete structural composition is far from exhausted and new solutions interesting from the engineering, scientific and aesthetic points of view of are constantly emerging.
Keywords: konstrukcje podwójnie zespolone; konstrukcje stalowo-betonowe; elementy rurobetonowe; structures of double composition; steel-concrete structures; concrete tubular members